1989
DOI: 10.1302/0301-620x.71b2.2925736
|View full text |Cite
|
Sign up to set email alerts
|

Radiological loosening after cemented hip replacement for juvenile chronic arthritis

Abstract: We reviewed the results of 14 total hip replacements in patients withjuvenile chronic arthritis. The mean age at operation was 16 years (range 12 to 22 years); follow-up was from four to 1 1 years (mean 8.5 years). Postoperatively pain relief was sustained in all but one hip, while movement generally remained significantly restricted. No hip has as yet required a revision operation, although eight hips (57%) show radiological changes suggestive of impending failure. All patients had severe polyarticular involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
7

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 10 publications
0
25
0
7
Order By: Relevance
“…Elsewhere it has been postulated that epiphyseal growth occurs by endo-cartilagenous ossification and at the diaphysis it occurs by radial expansion. 32 The authors suggested the high rate of loosening in young patients resulted from the bone surrounding the implant growing away from it. Osteopenia due to steroid use, disease and poor nutrition, as well as joint contractures altering the magnitude and direction of forces borne by the implant, have also been implicated in the high rates of loosening.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere it has been postulated that epiphyseal growth occurs by endo-cartilagenous ossification and at the diaphysis it occurs by radial expansion. 32 The authors suggested the high rate of loosening in young patients resulted from the bone surrounding the implant growing away from it. Osteopenia due to steroid use, disease and poor nutrition, as well as joint contractures altering the magnitude and direction of forces borne by the implant, have also been implicated in the high rates of loosening.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, very young patients (defined as those 30 years of age and younger [4]) have not experienced the same survivorship as their older counterparts. This has been attributed to an antiquated surgical technique and the use of THA in patients with juvenile rheumatoid arthritis [5,6,14,22,23,26]. However, it is unclear whether young patients have benefitted from improving outcomes afforded by contemporary THA.…”
Section: Introductionmentioning
confidence: 99%
“…Primary cemented THA in JIA has demonstrated in other reports an aseptic loosening rate of 19% to 57% at 5 to 10 years followup [4,23,27,38]. The survivorship of cementless primary THA in patients with JIA was reported to be 96% to 100% for the femoral stem and 88% to 90% for the acetabular cup at 5 to 13 years followup [20,21,30].…”
Section: Discussionmentioning
confidence: 95%